Blockchain-Based Supply Chain Management Using Machine Learning: Analyzing Decentralized Traceability and Transparency Solutions for Optimized Supply Chain Operations (Blockchain Technology and Distributed Systems, 2021)
Blockchain technology has revolutionized various industries by offering decentralized, transparent, and secure solutions. In the realm of supply chain management, blockchain's potential is further enhanced when combined with machine learning (ML). This paper provides a comprehensive analysis of blockchain-based supply chain management using ML, focusing on decentralized traceability and transparency solutions. We discuss how blockchain and ML integration can optimize supply chain operations, enhance traceability, and improve transparency. Key topics include the role of blockchain in establishing a decentralized ledger for supply chain data, ML algorithms for predictive analytics and anomaly detection, and the benefits of decentralized traceability and transparency in improving supply chain efficiency and reducing fraud. We also explore challenges such as scalability, interoperability, and data privacy, along with future prospects for this innovative approach.
Keywords: Blockchain; Machine Learning; Supply Chain Management; Traceability; Transparency; Decentralization; Predictive Analytics; Anomaly Detection; Efficiency; Fraud Reduction